Dynamic optimum design of a 3UPS-PRU parallel robot. (26th December 2016) - Zhao, Yongjie
This article deals with the methodology of the dynamic optimum design of the one translational and three rotational degrees of freedom parallel robots while considering the rigid-body dynamic property. The dynamic optimum design of the 3UP S-P RU (underlined P denotes an active prismatic joint driven by a servomotor) parallel robot is presented while considering the constraints on the installation dimension, joint rotation angle, and the interference. The maximum driving torque and the maximum driving power of the actuating joints are taken as the objective functions in the dynamic optimum design, respectively. The physical meanings of the objective functions are the maximum driving torque and the maximum driving power of the actuating joints when the moving platform translates along the z -axis in the maximum linear acceleration a max, rotates about an arbitrary axis in the maximum angular acceleration α max, translates along the z -axis in the maximum linear velocity v max, and rotates about an arbitrary axis in the maximum angular velocity ω max at the same time. The object of the dynamic optimum design is to minimize the maximum driving torque or the maximum driving power by employing worst case criterion. In the predefined design task, the results of the dynamic optimum design of the 3UP S-P RU parallel robot are the same when taking the maximum driving torque and the maximum driving power as the objective functions. The phenomenon can be verified by the fact that the distributions of the maximum driving torque and the maximum driving power are very similar to each other. The robot dimension has also been taken into account in the dynamic optimum design of the 3UP S-P RU parallel robot due to the consideration of the building cost and the miniaturization. The example of the dynamic optimum design of the 3UP S-P RU parallel robot is presented in the simulation. The conclusions are provided at the end of the article.